Empowerment of Community Creative Economy Through the Islamic Education Assembly (Majelis Taklim) - Handayani Indah Susanti (Journal of Islamic Economics and Finance Studies)
The activities of the Islamic Education Assembly require intervention in the form of empowerment through the strengthening of productive socio-economic capacities. In addition to focusing on its main activities in Islamic studies, the Islamic Education Assembly also organizes creative economic activities conducted by its members. However, these activities face challenges such as limited connections with external communities, dependency on others, and inadequate facilities and infrastructure that affect the effectiveness of community-based economic empowerment. This study aims to uncover the patterns and strategies of community economic empowerment used by the Islamic Education Assembly administrators and facilitators, as well as to identify the supporting and inhibiting factors in the empowerment process. The research adopts a qualitative approach, utilizing fieldwork through interviews, observations, and document analysis. The findings reveal that the empowerment process is carried out through a bottom-up approach based on the community's own initiatives. The Mezzo-Level Strategy was effectively implemented, focusing on empowering groups through education and training. Supporting factors include (a) high community participation, (b) loyalty of the congregation and community, (c) demands from congregants and members for training, (d) strategic location, and (e) flexible timing. Conversely, the key inhibiting factors are (a) limited connections with external communities, (b) dependency on others, and (c) inadequate facilities and infrastructure. These findings suggest that fostering community participation, strengthening institutional systems, and reducing dependency are critical for achieving sustainable community empowerment. The study highlights the potential of the Islamic Education Assembly to drive socio-economic development through creative economic activities tailored to local needs, provided the challenges are addressed strategically.